ESG INVESTMENT SCORE AND PORTFOLIO DIVERSIFICATION (E Global Congress, 2025)
ESG principles refer to the consideration of environmental, social and governance factors when evaluating companies. These principles allow investors to assess the long-term sustainability and social responsibility of companies. Companies that adhere to ESG principles often have high quality of management, social responsibility and environmental sustainability, which increases their financial stability.